Research of energy characteristics and fault position detection for cracked rotor system. (12th May 2023) - Zhang, Xiantao; Yang, Yongfeng; Gao, Ruize; Ming, Feng; Wang, Ping
Highlights: Applying the energy method to investigate the rotor system with crack faults. The influence of crack depth on the system's energy characteristics is achieved. The fault location can be accurately represented by using the proposed indicator. The theoretical results are in good agreement with the experimental tests. Abstract: Early crack faults will introduce subtle local changes in the whole rotor system, which may bring difficulties to the fault detection process due to external disturbing factors. Meanwhile, judging the damaged position of rotor systems might be tough only through displacement or velocity. To overcome these issues, the harmonic balance-energy power flow analysis (HB-EPFA) is presented to investigate the rotor system with a transverse crack. Besides, a novel indicator (Time-averaged power flow) is proposed to evaluate the crack faults. For the energy characteristic analysis, the cracked rotor appears a special amplitude-jumping phenomenon, even in the case of shallow crack depth. The influence of crack depth on power flow values under different rotating speeds is obtained. Furthermore, the existence of cracks will lead to the rotation shaft presenting an abrupt energy-changing zone, which can be used to detect crack position. Relevant experiments are applied to validate the proposed detection method, and the experimental results agree with the theoretical analysis. The conclusions achieved in this paper can provide a reference for fault diagnosis of rotor systems in engineering practice.